Experimental evidences for existence of varying moieties and functional groups in assorted crop waste derived organosolv lignins - Singh, Sandip K.; Dhepe, Paresh L. (Industrial Crops and Products, 2018)
Isolation of organosolv lignins (ORGLs, water:ethanol, 180 degrees C, 1 h, 93 +/- 5% mass balance) from various lignocellulosic materials like rice husk (RH), wheat straw (WS), bagasse (BG) & wood chips (WC) was done and experimental evidences are provided to perceive the differences in the structures of isolated lignins. To achieve this on bulk level, lignins were characterized by XRD, GPC, TGA & elemental analysis and on molecular level using UV-vis, ATR, 1D/2D HSQC NMR techniques. Besides isolated lignins, crop wastes and pulps were also characterized to divulge details on their properties. It was revealed that lignins have varying concentrations of sinapyl (S), coniferyl (G) and p-coumaryl alcohols (H) and tricin (T) moieties. While, Tricin (T) type lignin moieties are observed only in RH and WS derived lignins, RH derived lignin has higher concentration of side chains than other isolated lignins. Additionally, it is discovered that most lignins have G as main moiety.